Species profiles life histories and environmental requirements of coastal fishes and invertebrates (Mid-Atlantic)--Atlantic and shortnosed sturgeons - Gilbert, Carter R. (U.S. Department of the Interior, 1989)
U.S. Fish. Wildl. Serv. Biol. Rep. 82(11.122)